Giant Type IV Hiatal Hernia: Beyond Reflux, a Challenge for the Surgeon (Basic Health sciencies journal, 2025)
Grade IV hiatal hernia is a rare condition characterized by the intrathoracic migration of the stomach along with other abdominal viscera, such as the colon, spleen, or pancreas, through the esophageal hiatus. We present the case of a patient with long-standing symptoms of very severe epigastric pain who presented to the emergency department with exacerbation of the clinical condition. Imaging studies confirmed the presence of a giant hiatal hernia with multivisceral involvement. Surgical correction was performed laparoscopically, with reduction of the herniated contents and Hill-type gastroesophageal reflux disease (GERD). The postoperative course was favorable, with resolution of symptoms and adequate oral tolerance. This case highlights the importance of clinical suspicion, early diagnosis, and timely surgical treatment to prevent serious complications such as strangulation or perforation of herniated organs, as well as improving patient quality of life.
Keywords: Hiatal hernia; paraesophageal hernia; management; hernia repair